Morphological Comparison of Six Coastal Stream Populations of Crimean Barbel (Barbus tauricus Kessler, 1877) from the Southern Black Sea Basin - Ozpicak, M.; Polat, N. (Central Fisheries Research Inst Vali Adil Yazar Str. No:14Kasustu, Yomra, Trabzon x, 2019)
In this study we investigated possible morphological and biological differences among some populations of the Crimean Barbel Barbus tauricus Kessler, 1877 inhabiting Black Sea Region. The intraspecific variation of crimean barbel, on the basis of morphometric characters, was investigated. Samples caugth from six different coastal streams (streams Akçay, Terme, Engiz, Karadere, Solaklı and Değirmenağzı) between April 2015 and December 2016. A total of 311 samples were used in analysis. Length-weight (LWR) and morphological measurements-total length relationships, coefficient of variance were estimated according to localities. LWR show that B.tauricus has isometric growth most of the localities (b=3). Principle Component and Discriminant Function Analysis were used to calculate variations in populations. All relationships of the 29 morphological measurements were found significant in ANOVA results (P<0.001). According to DFA results fifteen morphometric measurements were used for clasification of populations with 92.3%. PCA analysis showed that six (PostDD, DPV, LCAUF, PrePD, DDC and PostPD) of the morphometric measurements are important for the populations. © 2019, Central Fisheries Research Inst. All rights reserved.
Keywords: DFA; Morphometric Characteristics; PCA; Turkey; Variation